Application of an Intensive Rehabilitation Program After Very Late Recovery of Consciousness: A Single-Case Neurorehabilitation and Neuroimaging Study. (April 2019) - Errante, Antonino; Saviola, Donatella; Fasano, Fabrizio; Basagni, Benedetta; Alinovi, Serena; Bosetti, Sara; Chiari, Margherita; Minardi, Rita; Pinardi, Chiara; Crisi, Girolamo; Fogassi, Leonardo; De Tanti, Antonio
Late recovery of consciousness in vegetative state is considered as an exceptional outcome and has been reported prevalently in patients who suffered a traumatic brain injury. In these patients, the benefits of prolonging the rehabilitation, aimed at the recovery of autonomy in basic everyday activities, has been demonstrated. Here, we describe the application of an intensive multi-professional rehabilitation program carried out on a young female patient, with exceptionally late recovery of consciousness, specifically, after 7 years of vegetative state due to severe brain hemorrhage. Neuropsychological and functional assessment was conducted before and after the end of the rehabilitation program. In addition, functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI)-based probabilistic tractography were performed. Two follow-up neuropsychological and functional assessments were also conducted 6 and 29 months after the conclusion of the program. Functional results showed an improvement, maintained over time, in walking with assistance, cognitive efficiency, visual acuity and visual field, dysarthria, and execution of activities of daily living. Moreover, functional and structural magnetic resonance imaging (MRI) data documented the existence of preserved neural networks involved in sensory, motor, and linguistic tasks, which in all likelihood support the recovery process. This report suggests the possibility of undertaking an intensive rehabilitation program in patients who remain for long periods in altered states of consciousness, in spite of early negative prognosis.